The Social Logic of Green Capitalism: Market Performance, Governance, and the Political Economy of Green Accounting in Indonesia - Iqwan Galfani; Shinta Melzatia (Baileo: Jurnal Sosial Humaniora, 2026)
This study investigates the social logic of green capitalism by examining how market performance, firm performance, and corporate governance influence green accounting practices in Indonesia’s energy and mining industries. Conducted on 40 companies listed on the Indonesia Stock Exchange from 2020 to 2024, this research adopts a purposive sampling method and employs panel data regression analysis using the EViews program. The findings reveal that corporate governance—measured through institutional ownership—has a positive and significant effect on green accounting, while market performance (measured by price to book value) and firm performance (measured by return on assets) show no significant influence. These results indicate that the adoption of green accounting in Indonesia’s extractive sector is not primarily driven by market or profitability incentives, but rather by governance mechanisms and institutional legitimacy. The study contributes to the sociology of economy by situating green accounting within the political economy of sustainability, where corporate environmental responsibility emerges as a negotiated outcome between economic rationality and social expectations. The novelty of this research lies in revealing the institutional embeddedness of green capitalism in emerging economies, demonstrating that environmental accountability is shaped more by governance ethics than by market efficiency. The study recommends that future sociological inquiries expand the analysis to cross-sectoral contexts and incorporate global regulatory pressures in modeling the evolution of green corporate behavior.